2018
DOI: 10.1155/2018/6712901
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Effect of Anti-TNF Therapy on Insulin Sensitivity in Nonobese, Nondiabetic Patients with Inflammatory Bowel Disease

Abstract: Background The aim of this study was to investigate the effect of anti-TNF therapy on glucose and lipid metabolism in nondiabetic, nonobese patients with inflammatory bowel disease (IBD). Patients and Methods We studied 44 patients with IBD, without a known history of diabetes. Three of the patients were diagnosed with overt diabetes and were excluded. Eighteen of the remaining patients (9 M/9 F, 33.6 ± 8.8 years) were on anti-TNF therapy for longer than 1 year, while 23 patients (16 M/7 F, 38.7 ± 12.5 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…As one of the markers of low‐grade inflammatory, white blood cell (WBC) is widely used in the evaluation of inflammation and metabolic related diseases because of its ease of monitoring and identification …”
Section: Introductionmentioning
confidence: 99%
“…As one of the markers of low‐grade inflammatory, white blood cell (WBC) is widely used in the evaluation of inflammation and metabolic related diseases because of its ease of monitoring and identification …”
Section: Introductionmentioning
confidence: 99%
“…7 With the advent of new drugs that enable better control of inflammatory activity and the establishment of treatment strategies with defined therapeutic targets, a reduction of the cardiovascular risk in this population is expected. A study conducted by Paschou et al 31 observed a decrease in insulin levels and homeostatic model assessment for insulin resistance index in patients with IBD after receiving treatment with biological therapy for a period of six months. These data suggest that clinical treatment can promote not only controlling intestinal inflammation, but also controlling risk factors for cardiovascular disease, resulting in the reduction of the overall risk of cardiovascular events in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α along with other released cytokines then targets endothelium, producing an impairment of vasorelaxation pathways and an increase in adhesion molecules that trigger leukocyte infiltration, both phenomena implicated in atherosclerosis initiation and progression (Steyers & Miller, 2014). Accordingly, the levels of the endothelium NO synthase inhibitor asymmetric dimethylarginine are higher in inflammatory bowel disease patients than in controls, and such increase correlates with platelet count and other inflammation parameters (Owczarek, Cibor, & Mach, 2010). Moreover, inflammatory bowel disease endothelium exhibits abnormally high levels of CD40 whereas soluble CD40 levels, produced by platelets, are also high in inflammatory bowel disease patients, reflecting an enhanced platelet activation state (Danese et al, 2003).…”
Section: Pathogenetic Mechanismsmentioning
confidence: 99%
“…More recently, anti‐TNF‐α agents, infliximab and adalimumab, were shown to lower plasma insulin levels and the homeostatic model assessment of insulin resistance index in inflammatory bowel disease patients. Hence, such drugs could reduce the risk of CVD (Paschou et al, 2018).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%